Children with wearable cardioverter defibrillators: Examining activity levels via accelerometer. (December 2019) - Huber, Nichelle L.; Burch, Ashley E.; Bianco, Nicole R.; Spar, David S.; Sears, Samuel F.
Abstract: The wearable cardioverter defibrillator can be used to protect against sudden cardiac arrhythmic death in at risk children. The wearable cardioverter defibrillator provides clinicians with multiple types of information such as activity level while wearing the device. The current study examined physical activity in pediatric populations while wearing the wearable cardioverter defibrillator and compared age, sex, and diagnostic groups in activity levels. The study sample included 231 children, aged 8–17, who wore a wearable cardioverter defibrillator between 2009 and 2017. All device based information and activity counts were retrieved from the data sent via remote monitoring. Pediatric patients were active for 73 min per day, with a median step count of 7361. These data were collected during their average of 39 days of wear time over an average of 21 h daily. There were no associations between sex, diagnostic groups, or end of use reason and wear time or activity; however, age was negatively associated with changes in activity level for patients aged 8–11. Results indicated significant increases in step count over the first three weeks of wear in all ages χ F 2 (3, n = 50) = 34.27, p < .001. Pediatric patients are relatively active and increase levels of physical activity over the first month of use. These results are encouraging in that pediatric patients with wearable cardioverter defibrillator are potentially improving both physically and mentally over time with the wearable cardioverter defibrillator. Highlights: Pediatric patients with WCDs are active for an average of 73 min daily. Activity levels were not influenced by sex or indication reason. Decreases in activity were noted from age 8 to 11 and then remained stable. Children significantly increase their activity level in first 30 days of WCD wear.